The illustrated guide to the Bible - Porter, J. R. (Joshua Roy) 1921- (Oxford Oxford University Press, 1995)
Examines the Biblical narratives in their historical, social, archaeological, and mythological contexts and provides a section with a book-by-book summary of the Bible.
Includes bibliographical references and index.
Keywords: Bible -- History of Biblical events; Bible; Bible; Jews -- Civilization -- To 70 A.D.; Palestine -- Civilization